Design of Chemo-entrepreneurship Oriented Teaching Materials to Analyze Students' Entrepreneurial Creativity - Maula Najikh Wildana; Sri Susilogati Sumarti; Endang Susilaningsih; Nuryanto Nuryanto (Journal of Educational Chemistry (JEC), 2022)
Studying Chemistry is not about the concept but how to train the students' creativity. The learning outcomes are influenced by several factors, including learning models and materials. Teachers still use the books provided by the school, so teachers should develop learning materials that suit learning objectives and students' conditions. Teachers should analyze the students' cognitive ability and also creativity. Chemo-entrepreneurship-oriented learning materials would help to analyze students' cognitive ability and entrepreneurial creativity. This research used research and development with ADDIE method. Results were the validity of material instrument from three experts gave very valid with the scores of 49, 50, and 48. The learning materials got a very good category from teachers' responses with a score of 34 out of 40 and got a good category from students' responses with a score of 38.53 out of 48. Results from the analysis of students' entrepreneurial creativity showed that students had high entrepreneurial creativity. Students also actively discussed and made creative products. There were aromatherapy candles, banana nuggets, apple donuts, and crispy balado potatoes.